2023
DOI: 10.3389/fsurg.2022.994775
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of phloroglucinol on pregnancy outcomes involving frozen embryo transfers in patients with endometriosis: A retrospective case-control study

Abstract: ObjectiveAbnormal contraction of uterus and vascular smooth muscle lead to the formation of hypoxia environment in uterus. Abnormal contraction may be the basis of dysmenorrhea, endometriosis, infertility and other diseases. Phloroglucinol is a non-atropine and non-papaverine smooth muscle spasmolytic agent, which can reduce the abnormal contraction of uterine smooth muscle. This study investigated the effect of phloroglucinol on frozen embryo transfer in patients with endometriosis.MethodsThe data of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…JZ contraction varies in different periods, showing contraction from the cervix to the fundus in the nonpregnant period and contraction from the fundus to the cervix during pregnancy. Abnormal uterine contraction may be the basis of important diseases such as dysmenorrhea, infertility, endometriosis, implantation failure, spontaneous inflammation, abortion, and premature babies ( 17 ). Based on the various stages of the menstrual cycle, many studies have shown changes in the magnitude, frequency, and direction of contractions in the uterine JZ of normal uterus and ADS ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…JZ contraction varies in different periods, showing contraction from the cervix to the fundus in the nonpregnant period and contraction from the fundus to the cervix during pregnancy. Abnormal uterine contraction may be the basis of important diseases such as dysmenorrhea, infertility, endometriosis, implantation failure, spontaneous inflammation, abortion, and premature babies ( 17 ). Based on the various stages of the menstrual cycle, many studies have shown changes in the magnitude, frequency, and direction of contractions in the uterine JZ of normal uterus and ADS ( 18 ).…”
Section: Introductionmentioning
confidence: 99%